Smart Urban Farming Based on Internet of Things Using Soil Moisture Control and Application of Liquid Fertilizer to Mustard - Mashuri; Muhammad Lukman Hakim; Achmad Zubaidi; Dika Andini Suryandari; Dimitra Meidina Kusnadi (Institut Teknologi Sepuluh Nopember, 2023)
Soil conditions significantly impact plant growth. Liquid fertilizer is used to optimize plant growth, and soil moisture is crucial too. Insufficient moisture causes withering, while excess leads to reduced soil oxygen. To monitor soil moisture, researchers developed an IoT-based Smart Urban Farming device using ESP32 microcontroller and 6 soil moisture sensors. The system operates through CNC Milling with X and Z axes movement. ADC pin on ESP32 reads sensor values, controlled and monitored by thinger.io. The device can work automatically or manually. Input and output testing ensures performance assessment. Soil moisture sensor testing yields 2091-3998 bits range, stepper motor testing shows 1.96% highest error, and water pump testing takes 0.05 seconds/milliliter. Mustard plants use a 60% set point for soil moisture, and the pump activates at 55%. The device shows good performance with an error range of 0.03% - 0.08%, demonstrating the effectiveness of the smart urban farming system.